(untitled) (Cadernos de Sociomuseologia, 2019)
From the experience of working as a trainee in the projects of the Ethnology and Ethnography Sector of the National Museum of Rio de Janeiro (SEE / MN), from 2013 to 2017, and from training as a Master in Preservation of Collections (PPACT / MAST), a small analysis of the losses and damages of the collection of ethnology of the National Museum after the fire of September 2018. It then presents a brief discussion and lists a set of basic measures for preservation and security of cultural assets in case of fire accidents; and in the context of the preservation and digitization projects of the SEE / MN collection, brings the suggestion of digital curation and the creation of a Digital Preservation Policy as a way to preserve the remaining records of the sector’s collection. Key-words: National Museum. Ethnographic collections. Claims with fire. Digital preservation